Developing Critical Thinking Indicators and Research Trends in Islamic Religious Education with VOSviewer - Rihlah Nur Aulia; Yasnita Yasnita; Amaliyah Amaliyah (Universitas Negeri Jakarta, 2024)
This research aims to develop indicators of students' critical thinking and find the state of the art by using Vos Viewer. One way to develop critical thinking indicators is through research. The teacher's job besides teaching is to conduct research. Research is said to be good if it finds elements of new findings so that it has a contribution both to science and to life. One of the difficulties in research is finding novelty, nowadays with the Vos Viewer application it is easy to find the novelty of a research variable, such as the critical thinking variable. The research subject is students in Islamic educational institutions. The object or focus of the research is to develop indicators of students' critical thinking in learning Islamic religious education. In addition, the research aims to analyze the opportunities and development of research trends related to critical thinking in Islamic learning. This research is important as a way to help Islamic religious education teachers develop critical thinking indicators as an effort to familiarize students with reading literacy and numeracy in accordance with the demands of the independent curriculum. The method used is bibliometric by collecting article data from 2018-2022 through Google Scholar and Scopus sites with Publish or Perish software for 1,000 journals. The results of the study describe that critical thinking indicators can be developed through familiarizing students with analyzing, evaluating, and analyzing.